DIVISION I: COMMISSION 8: ASTROMETRY. (13th August 2015) - Evans, Dafydd Wyn; Zacharias, Norbert; Kumkova, Irina; Andrei, Alexandre; Brown, Anthony; Gouda, Naoteru; Popescu, Petre; Souchay, Jean; Unwin, Stephen; Zhu, Zi
Abstract : The business meeting was opened by the President, Dafydd Evans, who presented the agenda, which was approved. It was agreed that Norbert Zacharias should be the secretary of the meeting and take the minutes. This session was attended by about 20 participants.